Risk factors for febrile urinary tract infection in boys with posterior urethral valves - Harper, Luke; Botto, Nathalie; Peycelon, Matthieu; Michel, Jean-Luc; Leclair, Marc-David; Garnier, Sarah; Clermidi, Pauline; Arnaud, Alexis P.; Dariel, Anne-Laure; Dobremez, Eric; Faure, Alice; Fourcade, Laurent; et al. (Frontiers in Pediatrics, 2022)
Objective Boys with posterior urethral valves (PUV) present an increased risk of febrile urinary tract infection (fUTI). Identifying specific risk factors could allow for tailoring UTI prevention. We performed a secondary analysis of the CIRCUP randomized controlled trial data to identify patient characteristics associated with a higher risk of fUTI. Patients and Methods We performed a secondary analysis of the data from the CIRCUP randomized trial which included boys with PUV, randomized to circumcision and antibiotic prophylaxis vs antibiotic prophylaxis alone and followed for 2 years. There was only 1 episode of fUTI in the circumcision group vs 17 in the uncircumcised group. We therefore only studied the antibiotic prophylaxis alone group and compared age, size and weight at birth, presence of dilating VUR at diagnosis, presence of dysplasia on DMSA scan at 2 months, and nadir creatinine between children who presented a fUTI and those who did not, as well as age at first episode of fUTI. Results The study group consisted of 42 patients of which 17 presented at least on fUTI. Presence of dilating VUR was significantly associated with risk of fUTI (p=0.03), OR: 5.57 (CI95% = [1.13-27.52]). None of the other parameters were associated with increased risk of fUTI. We observed three distinct time periods for presenting a fUTI with a decrease in infection rate after the first 40 days of life, then at 240 days of life. Conclusion Febrile UTI prevention in boys with PUV could be tailored to circumcision status and presence of high-grade VUR. The rate of febrile UTIs seems to decrease after 9 months.